The genus Minettia Robineau-Desvoidy, 1830 (Diptera: Lauxaniidae: Lauxaniinae) from the Oriental Region with descriptions of seventeen new species - Li, Wenliang; Bai, Yingming; Yang, Ding (Zootaxa, 2023)
Seventeen species of Minettia Robineau-Desvoidy, 1830 from Southwest China are described as new to science: Minettia (Plesiominettia) bicolorata sp. nov., M. (P.) caii sp. nov., M. (P.) cuiae sp. nov., M. (P.) dulongjiangensis sp. nov., M. (P.) huangi sp. nov., M. (P.) ludingensis sp. nov., M. (P.) mediclavata sp. nov., M. (P.) nujiangensis sp. nov., M. (P.) orbitalis sp. nov., M. (P.) prominens sp. nov., M. (P.) spiniphallata sp. nov., M. (P.) surstylata sp. nov., M. (Minettia) annulifera sp. nov., M. (M.) baii sp. nov., M. (M.) scutellata sp. nov., M. (M.) terminalis sp. nov. and M. baihualingensis sp. nov. The new species M. baihualingensis sp. nov. cannot be classified under one of the five known subgenera because of its unique characteristics. Keys to separate world species of the subgenus Plesiominettia and Oriental species of the subgenus Minettia are presented.